PENGEMBANGAN PERANGKAT PEMBELAJARAN MULTILEVEL DENGAN PENDEKATAN PROBLEM SOLVING UNTUK MENINGKATKAN SIKAP DAN PRESTASI BELAJAR MATEMATIKA PADA MATERI LINGKARAN SISWA MTs. QAMARUL HUDA TAHUN 2019 - Supratman, Moh. (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2020)
This study aims to produce mathematical learning tools with a problem-solving approach that is feasible to use to improve students' mathematics learning attitudes and achievement with different abilities in the Circle material. Products consist of syllabus, lesson plans, and multilevel worksheets. Product quality and eligibility refers to Nieveen's validity, practicality, and effectiveness criteria. The development procedure adapted the Borg & Gall development research model and was modified in five stages of development, including the stages: preliminary studies, initial product development, validation, testing, and revision of the final product. Data collection instruments include: validation sheets, teacher assessments, and student opinions, mathematics attitude questionnaires, and pretest-posttest scripts. Data in the form of standard scores were analyzed using norm reference benchmarks. Data in the form of comments and suggestions were analyzed descriptively qualitatively and concluded as material for product revision. Learning outcomes test data were analyzed by benchmark reference assessment. The research resulted in a multilevel mathematics learning tool product with a problem-solving approach that was feasible to use. Product eligibility is based on validation results that classify highly valid products and trial results which show that the product is very practical and effective in improving students' mathematical attitudes and learning achievements.